RELATIONSHIP WITH THE MOTIVATION TO BE NURSE LABORATORY PRACTICE SKILLS AKPER MAMBAUL ULUM SURAKARTA - Nurhaya, Isnani (JURNAL PROFESI || MEDIA PUBLIKASI PENELITIAN, 2014)
The quality nursing Diploma graduates are skilled and least visible when dealing with patien. The emergency problems assosiated with the lack of quality of the selection system is receiving less attention to the motivation to be a nurse from prospectives students. The second is less skill in handling cases of nursing practice in the hospital so that students are less confident and less skilled in performing the procedure act. The purpose of this research was to analyze the relationship between motivation to be a nurse and nursing skills laboratory practice courses I basic human needs. The study was quantitative research with cross sectional approach. The population was first rate student, using simple random sampling. Validity and reliability was tested by using Product Moment test and Alpha Chonbrach. Data analysis by using the Product Moment Chorelation hypotesis one and two Followed Dual Linear Regression on three hypotheses with the significant level of 5%. Data collection by questionnaire. The conclusions of this study, there was no relationship between motivation to be anurse and the nursing skills laboratory practice (r = 0.151, p> 0.05). Â  Keywords: Motivation, practical laboratory skills